Trek Across Maine 25th Anniversary: A Public Health Strategy to Increase Physical Activity. Issue 5 (September 2013) - Martin, Sarah Levin; Martin, Maurice; Perry, Tess; Harris, Jessica Maureen
Could an annual event be an effective strategy to improve physical activity? Based on 25 years of data, we argue that it could be. Although there are eight recommended strategies to promote physical activity in the Community Guide, there is insufficient evidence for six others. Qualitative data collected from Trek Across Maine participants and other cause-specific events suggests that goal setting (i.e., individually adapted health behavior change) and family-based social support may be key factors in helping individuals become more physically active.